Sodium butyrate attenuates high-fat diet-induced steatohepatitis in mice by improving gut microbiota and gastrointestinal barrier - Zhou, Da; Pan, Qin; Xin, Feng-Zhi; Zhang, Rui-Nan; He, Chong-Xin; Chen, Guang-Yu; Liu, Chang; Chen, Yuan-Wen; Fan, Jian-Gao (World journal of gastroenterology : WJG, 2017)
AIM To investigate whether gut microbiota metabolite sodium butyrate(Na B)is an effective substance for attenuating non-alcoholic fatty liver disease(NAFLD)and the internal mechanisms.METHODS Male C57BL/6J mice were divided into three groups,normal control were fed standard chow and model group were fed a high-fat diet(HFD)for 16 wk,the intervention group were fed HFD for 16 wk and treated with Na B for 8 wk.Gut microbiota from each group were detected at baseline and at 16 wk,liver histology were evaluated and gastrointestinal barrier indicator such as zonula occluden-1(ZO-1)were detected by immunohistochemistry and realtime-PCR,further serum or liver endotoxin were determined by ELISA and inflammation-or metabolism-associated genes were quantified by real-time PCR.RESULTS Na B corrected the HFD-induced gut microbiota imbalance in mice,while it considerably elevated the abundances of the beneficial bacteria Christensenellaceae,Blautia and Lactobacil us.These bacteria can produce butyric acid in what seems like a virtuous circle.And butyrate restored HFD induced intestinal mucosa damage,increased the expression of ZO-1 in small intestine,further decreased the levels of gut endotoxin in serum and liver compared with HF group.Endotoxin-associated genes such as TLR4 and Myd88,pro-inflammation genes such as MCP-1,TNF-α,IL-1,IL-2,IL-6 and IFN-γin liver or epididymal fat were obviously downregulated after Na B intervention.Liver inflammation and fat accumulation were ameliorated,the levels of TG and cholesterol in liver were decreased after Na B intervention,NAS score was significantly decreased,metabolic indices such as FBG and HOMA-IR and liver function indicators ALT and AST were improved compared with HF group.CONCLUSION Na B may restore the dysbiosis of gut microbiota to attenuate steatohepatitis,which is suggested to be a potential gut microbiota modulator and therapeutic substance for NAFLD.